Assessing social–ecological feedbacks in small-scale fisheries - Leandro Castello; Adriana Guimarães Abreu; George Christopher Brooks; João Vitor Campos-Silva; Priscila dos Reis Cunha; Ayan Santos Fleischmann; Caetano Lucas Borges Franco; Ana Claudia Gonçalves; Emma Ann Hultin; Holly Kathleen Kindsvater; Eduardo Guimarães Martins; Cristina Isis Buck Silva; et al. (Ambio, 2026)
Assessment frameworks do not capture the complexity of the social–ecological dynamics of small-scale fisheries (SSF), which support millions of livelihoods yet face persistent sustainability challenges. Reciprocal feedbacks between fish populations and fishers that are central to sustainability remain insufficiently integrated into assessment approaches because conventional fisheries management emphasizes population dynamics, whereas social–ecological systems research focuses on social drivers and faces operational challenges. We propose an integrative diagnostic approach that explicitly links fish population dynamics with theories of fisher behavior and governance. We illustrate its application using co-managed arapaima fisheries in the Amazon Basin, where sustainability emerges from multi-scalar social and ecological interactions. By capturing these feedbacks, the approach bridges ecological and social dimensions to identify key drivers of sustainability. It provides a replicable, interdisciplinary framework for diagnosing SSF sustainability and identifying leverage points to support adaptive governance across diverse contexts.